Penerapan Software Inlislite pada Pengolahan Bahan Pustaka di Dinas Perpustakaan dan Kearsipan Provinsi Sulawesi Selatan - Hidayat, Nurul; Iskandar; Mulyadi, Irvan (Literatify: Trends in Library Developments, 2024)
The main problem in this research is how to apply Inlislite software to the processing of library materials at the Library and Archives Service of South Sulawesi Province. From the main problem above the author divides it into two sub-problems, namely: First, how to apply Inlislite software to the processing of library materials at the Library Service and South Sulawesi Provincial Archives. Second, what are the obstacles faced in implementing Inlislite software in processing library materials at the South Sulawesi Province Library and Archives Service. The type of research used is qualitative descriptive research with a systematic managerial approach. The results of this research indicate that the implementation of the inlislite application at the South Sulawesi Province Library and Archives Service has been carried out well. There are two ways to process library materials, namely manual processing and automated processing. Obstacles faced by librarians in implementing applications include frequent maintenance and very limited budgets.